Supplementing L-Citrulline Can Extend Lifespan in C. elegans and Attenuate the Development of Aging-Related Impairments of Glucose Tolerance and Intestinal Barrier in Mice - Dragana Rajcic; Franziska Kromm; Angélica Hernández-Arriaga; Annette Brandt; Anja Baumann; Raphaela Staltner; Amélia Camarinha-Silva; Ina Bergheim (Biomolecules, 2023)
L-Citrulline (L-Cit) is discussed to possess a protective effect on intestinal barrier dysfunction but also to diminish aging-associated degenerative processes. Here, the effects of L-Cit on lifespan were assessed in C. elegans, while the effects of L-Cit on aging-associated decline were determined in C57BL/6J mice. For lifespan analysis, C. elegans were treated with ±5 mM L-Cit. Twelve-month-old male C57BL/6J mice (n = 8–10/group) fed a standard chow diet received drinking water ± 2.5 g/kg/d L-Cit or 5 g/kg/d hydrolyzed soy protein (Iso-N-control) for 16 or 32 weeks. Additionally, 4-month-old C57BL/6J mice were treated accordingly for 8 weeks. Markers of senescence, glucose tolerance, intestinal barrier function, and intestinal microbiota composition were analyzed in mice. L-Cit treatment significantly extended the lifespan of C. elegans. The significant increase in markers of senescence and signs of impaired glucose tolerance found in 16- and 20-month-old control mice was attenuated in L-Cit-fed mice, which was associated with protection from intestinal barrier dysfunction and a decrease in NO2− levels in the small intestine, while no marked differences in intestinal microbiota composition were found when comparing age-matched groups. Our results suggest that pharmacological doses of L-Cit may have beneficial effects on lifespan in C. elegans and aging-associated decline in mice.